Sialyllactose Enhances the Short-Chain Fatty Acid Production and Barrier Function of Gut Epithelial Cells via Nonbifidogenic Modification of the Fecal Microbiome in Human Adults - Yohei Sato; Masaya Kanayama; Shiori Nakajima; Yukihiro Hishida; Yuta Watanabe (Microorganisms, 2024)
Although various benefits of human milk oligosaccharides (HMOs) have been reported, such as promoting Bifidobacterium growth in the infant gut, their effects on adults have not been fully studied. This study investigated the effects of two types of sialyllactose, 3′-sialyllactose (3′-SL) and 6′-sialyllactose (6′-SL), on the adult intestinal microbiome using the simulator of human intestinal microbial ecosystem (SHIME®), which can simulate human gastrointestinal conditions. HPLC metabolite analysis showed that sialyllactose (SL) supplementation increased the short-chain fatty acid content of SHIME culture broth. Moreover, 16S rRNA gene sequencing analysis revealed that SL promoted the growth of Phascolarctobacterium and Lachnospiraceae, short-chain fatty acid-producing bacteria, but not the growth of Bifidobacterium. Altogether, both types of SL stimulated an increase in short-chain fatty acids, including propionate and butyrate. Additionally, SHIME culture supernatant supplemented with SL improved the intestinal barrier function in Caco-2 cell monolayers. These results suggest that SL could act as a unique prebiotic among other HMOs with a nonbifidogenic effect, resulting in intestinal barrier protection.